Opioid-related Emergency Department Visits During COVID-19 in a Large Health System. Issue 4 (July 2021) - Hall, Gavin T.; Cruz, Daniel S.; Lank, Patrick M.; McCarthy, Danielle M.; Kim, Howard S.
Abstract : Objective: Multiple states have reported increases in opioid overdose deaths during the coronavirus disease 2019 (COVID-19) pandemic, however little is known about opioid-related presentations to the emergency department (ED). Methods: This was a time series analysis of visits to 7 EDs in greater Chicago, Illinois from October 20, 2019 to July 25, 2020. We compared the number of ED visits for opioid-related diagnoses in the time period preceding the World Health Organization pandemic declaration (prepandemic period, October 20, 2019–July 3, 2020) to the time period following the World Health Organization declaration (pandemic period, March 8, 2020 to July 25, 2020) using a single-group interrupted time series analysis with Newey-West standard errors. We also present data on alcohol-related ED visits for comparison. Results: We evaluated a total of 177, 405 visits across the 7 EDs during the study period. The mean number of weekly ED visits in the prepandemic and pandemic periods was 4841 and 4029 weekly visits, respectively. In the interrupted time series analysis, there was no significant immediate effect of the pandemic start on opioid-related ED visits (−0.44 visits per 1000 ED visits, 95% CI −2.47 to 1.58, P  = 0.66), however, there was a significant immediate effect of the pandemic start on alcohol-related ED visits (−4.1, 95% CI: −8.25 to −0.01, P  < 0.05). Conclusions: Despite reductions in overall ED visit volumes and alcohol-related visits during COVID-19, the number of opioid-related visits was not significantly reduced during the early pandemic. These data reinforce the need to provide comprehensive treatment services for opioid use disorder during the co-occurring COVID-19 and opioid crises. Abstract : Supplemental Digital Content is available in the text